Long-term tooth retention in periodontitis patients in four German university centres - Graetz, Christian; Bäumer, Amelie; Eickholz, Peter; Kocher, T.; Petsos, H.; Pretzl, Bernadette; Schwendicke, F.; Holtfreter, B. (Journal of dentistry, 2020)
Objectives: In this retrospective study, we compared tooth loss between patients receiving periodontal therapy (PT) in four German university centres, stratified according to periodontal treatment phase. Materials and Methods: Overall, 896 patients (Kiel (KI) n=391; Greifswald (GW) n=282; Heidelberg (HD) n=174; Frankfurt a.M. (F) n=49) were examined initially (T0), after active periodontal therapy (APT, T1) and after supportive periodontal therapy (SPT, T2). Descriptive analyses and multivariable negative binomial regression models were performed. Results: Follow-up periods differed significantly between the centres, ranging between 6.7±3.0 (GW) and 18.2±5.5 (KI) years (p<0.001). At T0, age, gender, smoking and diabetes showed notable regional distinctions (p<0.001). However, the number of teeth per patient was similar (between 24.0±4.6 (F) and 24.5±4.1 (HD); p=0.27). During PT, the number of extracted teeth differed significantly between centres, with greater differences during SPT (0.9±1.8 (GW) to 2.3±2.8 (KI), p<0.001) compared to APT (0.4±0.9 (F) to 1.0±2.1 (KI), p=0.02). Annual tooth loss during SPT remained low in all centres (between 0.10±0.14 (F) to 0.15±0.30 (HD), p<0.001). Conclusion: Within the limitation of the study, PT leads to a low risk of tooth loss in all university centres irrespective of patients’ baseline characteristics.Clinical Relevance: Within the limitations of this retrospective investigation, long-term tooth retention seems to be feasible for most patients, as long as a systematic and structured treatment approach is applied.